Flow-induced vibration of a circular cylinder with rigid splitter plate. (August 2019) - Sahu, Tulsi Ram; Furquan, Mohd; Jaiswal, Yash; Mittal, Sanjay
Abstract: Flow-induced vibration (FIV) of a circular cylinder with an attached rigid splitter plate is studied. A stabilized finite element formulation is utilized to solve the incompressible flow equations in two-dimensions. Three regimes of FIV are identified for the range of reduced speed ( 1 ≤ U ∗ ≤ 70 ) studied: vortex-induced vibration (VIV), steady flow and galloping. The effect of mass ratio, 2 ≤ m ∗ ≤ 1000, is studied for the R e = 150 flow (Reynolds number is based on diameter of the cylinder, D ) and splitter plate of length, L p = 3 . 5 D . In contrast to an isolated cylinder, the peak response of the cylinder with splitter plate is associated with a significantly smaller amplitude and the lock-in occurs over a wider range of U ∗ . The U ∗ for the onset of lock-in increases with increase in m ∗ . The end of lock-in, however, is independent of m ∗ . In addition, unlike the isolated cylinder, the transition from desynchronization to lock-in is gradual, except for very large m ∗ . Although galloping occurs for all m ∗, its onset is strongly dependent on m ∗ . The end of lock-in regime of VIV is immediately followed by onset of galloping for small m ∗ . For this range of m ∗, the galloping is strongly influenced by vortex shedding. A steady regime, wherein the vibration is completely suppressed for a certain range of U ∗, occurs beyond the lock-in regime for moderate m ∗ . However, galloping eventually ensues and revives the unsteadiness at large U ∗ . For very large m ∗, the steady flow regime is replaced by a desynchronization region. In general, the onset of galloping is delayed to larger U ∗ with increase in m ∗ . The effect of the length of the splitter plate ( L p ∕ D = 1 . 5, 2.5 and 3.5) on FIV is studied for m ∗ = 10 . The steady flow regime is observed only for L p = 3 . 5 D . Increase in L p leads to a small increase in the peak amplitude and range of lock-in during VIV. The effect on galloping is more significant; the amplitude of vibration, at a given U ∗, decreases with increase in L p . The frequency of vibration decreases, during both VIV and galloping, with increase in L p . The effect of R e, within the laminar regime, is studied. Its effect on the amplitude of vibration is found to be similar to that of L p . Graphical abstract: Highlights: Flow-induced vibration of circular cylinder with a rigid splitter plate. Three regimes of FIV: VIV, steady flow and galloping. Effect of mass ratio, plate length and Re on response during different regimes. VIV galloping interaction for low mass ratio. Steady flow and classical galloping for high mass ratio.